Frequency of BRAF V600E Mutation in the Mexican Population of Patients With Metastatic Melanoma - Ruiz-Garcia, Erika (J Glob Oncol, 2017)
PURPOSE: The BRAF V600E mutation has been described in melanomas occurring in the Caucasian, European, and Asian populations. However, in the Mexican population, the status and clinical significance of BRAF mutation has not been researched on a large scale. METHODS: Consecutive BRAF-tested Mexican patients with metastatic melanoma (n = 127) were analyzed for mutations in exon 15 of the BRAF gene in genomic DNA by real-time polymerase chain reaction technology for amplification and detection. The results were correlated with the clinical-pathologic features and the prognosis of the patients. RESULTS: The frequency of somatic mutation V600E within the BRAF gene was 54.6% (43 of 127 patients). Nodular melanoma was the most prevalent subtype in our population, with BRAF mutations in 37.2% (16 of 55 patients). In contrast, superficial spread had a frequency of 18.6% BRAF mutation (eight of 24). Other clinicopathologic features were assessed to correlate with the mutation status. CONCLUSION: This study searched for the most prevalent BRAF V600E mutation type in melanoma in a heterogeneous population from Mexico. Nodular melanoma was found to be the most prevalent in metastatic presentation and the presence of BRAF V600E mutation, perhaps related to the mixed ancestry; in the north, ancestry is predominantly European and in the south, it is predominantly Asian. The outcomes of the mutation correlations were similar to those found in other populations.